The Association Between Dietary Intake and Improvement of LARS Among Rectal Cancer Patients After Sphincter-Saving Surgery-A Descriptive Cohort Study - Liu, Wen; xia, haiou (Frontiers in Surgery, 2022)
Background: Dietary management was an important strategy for controlling low anterior resection syndrome (LARS) after sphincter-saving surgery, however, the influencing dietary factors of LARS are not completely clear.This study aims at exploring the specific association between perioperative intake of foods and nutrients and the improvement of LARS within the first 6 months after surgery. Methods: This study applied a prospective cohort design. 210 consecutive patients were admitted in the colorectal surgical ward after the sphincter-saving surgery in a tertiary hospital in China from May to November in 2020. The perioperative food intake was assccessed by the food frequency questionnaire，and the bowel symptoms were assccessed by the Low Anterior Resection Syndrome Score Scale. The binary logistic regression was used to analyze the collected data. Results: It was found out that both the intake of oil before surgery and at 6 months after surgery were significantly associated with the improvement of LARS. The average daily intake of lLivestock and poultry meats and oil during the first 6 months after the sphincter-saving surgery were also associated with the improvement of LARS. Conclusions: The relationship between the intake of Livestock and poultry meats and oil foods and the improvement of LARS was significantsignificant in this study. It provides evidence for medical staff to make up effective interventions of moderating the intake of specific food and nutrientdiet to promote the improvement of LARSpromote the relief of LARS during the first 6 months after sphincter-saving surgery.